Respostas
respondido por:
1
a)
0²-5•0+1
0-5+1
1
b)
2²-5•2+1
4-10+1
-5
c)
-1²-5•-1+1
1+5+1
7
0²-5•0+1
0-5+1
1
b)
2²-5•2+1
4-10+1
-5
c)
-1²-5•-1+1
1+5+1
7
respondido por:
1
x² - 5x + 1
a)
x = 0
x² - 5x + 1 = 0² - 5.0 + 1 = 1
b)
x = 2
x² - 5x + 1 = 2² - 5.2 + 1 = 4 - 10 + 1 = 5 - 10 = - 5
c)
x = - 1
x² - 5x + 1 = (-1)² - 5.(-1) + 1 = 1 + 5 + 1 = 7
a)
x = 0
x² - 5x + 1 = 0² - 5.0 + 1 = 1
b)
x = 2
x² - 5x + 1 = 2² - 5.2 + 1 = 4 - 10 + 1 = 5 - 10 = - 5
c)
x = - 1
x² - 5x + 1 = (-1)² - 5.(-1) + 1 = 1 + 5 + 1 = 7
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás